Water and city. Proposals for the construction of an interdisciplinary methodology in the approach to the relationships between people and the environment - Argañaraz, Cecilia Magdalena (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2020)
This work has as main objective to present a methodological construction process that can be described as interdisciplinary. It is intended to go through the process whereby the initial methodological research questions and choices, constructed from a disciplinary logic, were linked to methodological tools from other disciplines. Presenting the first steps of this unfinished process, it is also intended to highlight the coincidences between methodological lines that have been developed by various social scientists, in which an operation or an investigative attitude described as “tracking” is claimed, which can be considered a bridge methodological between disciplinary lines of research. This exploration is illustrated by presenting the first results of an ongoing investigation, whose theme is the historical evolution of the links between water and city in San Fernando del Valle de Catamarca (Catamarca, Argentina). Next, some challenges and possible indications are rescued to continue complexing the theoretical-methodological construction proposed.